PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, KECERDASAN INTELEKTUAL TERHADAP PEMAHAMAN AKUNTANSI (Studi Empiris Pada Mahasiswa Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Moch Syaifudin; Nur Diana; Hariri Hariri (Universitas Islam Malang, 2021)
This research was conducted with the aim of knowing the effect of emotional intelligence, spiritual intelligence, and learning behavior on the level of accounting understanding either partially or simultaneously. This research is included in a quantitative research approach that focuses on hypothesis testing, data collection in this study uses a questionnaire distributed to students. The population in this study were undergraduate accounting students class 2017 and 2018 at the Islamic University of Malang, with a total sample of 110 respondents, the sample was selected using the purposive sampling method. The results of this study indicate that partially emotional intelligence has a negative effect on the level of accounting understanding with a significant value. 0.011 <0.05, spiritual intelligence has no significant effect on the level of accounting understanding with a significance value of 0.059 <0.05, intellectual intelligence has no significant effect on the level of accounting understanding with a significance value of 0.395 <0.05. Simultaneously emotional intelligence, spiritual intelligence, and intellectual intelligence significantly influence the level of accounting understanding with a significance value (0.046 <0.05).Keywords : emotional intelligence, spiritual intelligence, and learning behavior